PEDAGOGICAL PRACTICE AS THE MAIN FACTOR FORMING THE PROFESSIONAL COMPETENCES OF THE FUTURE MUSIC TEACHER - Mukhitdinova, Malokhat (Журнал иностранных языков и лингвистики, 2022)
The article discusses the features of the organization and implementation of the pedagogical practice of students of music education in the context of the implementation of the competency-based model of professional training. The basic principles of updating its content are shown. The university focuses on creating a professional educational environment that activates the competency-based qualities of a future music teacher.